3
$\begingroup$

The problem is to find the derivative of $f(x) = \frac{3x}{x^2+1}$ at $x = -4$ using the limit definition, $$ f'(x) = \lim_{h\to 0}\frac{f(x+h)-f(x)}{h} $$

Progress

I plug in $-4$ for $x$ when using the limit definition and I always end up stuck with an unfactorable denominator. I tried it $5$ times already but I always end up with the same denominator.

$$\frac{-45 + 12h}{17 (h^2 - 8h + 17)}$$

$\endgroup$
  • $\begingroup$ When you have that at the end, you can safely plug in $h=0$, because it's not an indeterminate form (i.e. it's not $\dfrac00$). $\endgroup$ – Akiva Weinberger Sep 3 '14 at 1:21
1
$\begingroup$

If you want to find $$\lim_{h\rightarrow 0}\frac{-45 + 12h}{17 (h^2 - 8h + 17)}$$ as $h$ approaches $0$ the you can see that it becomes (since the numerator and denominator are such that when $h$ is $0$ we don't end up with and indeterminate form): $$ -\frac{45}{17\times17} =-\frac{45}{289}$$ Which if you work out the derivative normally you can see that this is the case since: $$ f'(x)=-\frac{3 \left(x^2-1\right)}{\left(x^2+1\right)^2} \;\; \therefore \;\; f'(4)=-\frac{45}{289}$$


Just as an extension to the above you can see that in general you have: $$f'(x)=\frac{\frac{3 (h+x)}{(h+x)^2+1}-\frac{3 x}{x^2+1}}{h} \;\;\; \text{which can simplify to}\;\; -\frac{3 (x (h+x)-1)}{\left(x^2+1\right) \left((h+x)^2+1\right)} $$ which again if you let $h=0$ then you can see that it becomes: $$f'(x)=-\frac{3 (x (0+x)-1)}{\left(x^2+1\right) \left((0+x)^2+1\right)}=-\frac{3 (x^2-1)}{\left(x^2+1\right) \left(x^2+1\right)}=-\frac{3 \left(x^2-1\right)}{\left(x^2+1\right)^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.